PENGEMBANGAN RANCANGAN PENGUATAN KAPASITAS PRECEPTOR KLINIS MELALUI KAJIAN GAP KOMPETENSI DI RUMAH SAKIT UMUM DAERAH CIBABAT CIMAHI MENUJU RUMAH SAKIT PENDIDIKAN - Haryanto, Mokhamad Sandi; n Sumarni, Tintin; Susilaningsih, F. Sri; Murtiningsih, Murtiningsih (JURNAL KEPERAWATAN, 2024)
Background:Preceptors play an important role in clinical guidance, namely guiding andeducating preceptees to become professional nurses. Preceptors have duties as educators andclinical officers who are often constrained by time and workload. When teaching, preceptorsneed methods or strategies so that learning objectives can be achieved and are effective.Objective: The aim is to analyze the competency gap for Clinical Nurses 3 in clinical guidancecapacity at Cibabat Cimahi Regional Hospital. Method: The design of this research is actionresearch. Taking total sampling, the research reached stage 2 of the 4 stages of actionresearch.Results: the results of Clinical Nurses 3 , Nurse Competency in implementing clinicalguidance for students are still low. Part A regarding student evaluation, the average score is31.319 with 22 people with high competency and 25 people with low competency. Part B isabout determining individual goals and teaching, the average score is 42.1 with 17 people withhigh competency and 30 people with low competency. Part C is about determining teachingstrategies, the average score is 60.8 with 18 people with high competency and 29 people withlow competency. Part D regarding knowledge demonstrations held, the average score was 17with 20 people with high competency and 27 people with low competency. Conclusion: Thereis a clinical competency gap in Clinical Nurses 3 Keywords: Competency Gaps; Mentors; Reinforcement design